2012
DOI: 10.4049/jimmunol.1200802
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Plasmacytoid Dendritic Cell Migration to the Splenic White Pulp Is Cooperatively Regulated by CCR7- and CXCR4-Mediated Signaling

Abstract: Although the spleen plays an important role in host defense against infection, the mechanism underlying the migration of the innate immune cells, plasmacytoid dendritic cells (pDCs), into the spleen remains ill defined. In this article, we report that pDCs constitutively migrate into the splenic white pulp (WP) in a manner dependent on the chemokine receptors CCR7 and CXCR4. In CCR7-deficient mice and CCR7 ligand-deficient mice, compared with wild-type (WT) mice, substantially fewer pDCs were found in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…The chemotactic effects of CXCL12 on T cells is well established, yet whether active CXCL12 is soluble, immobilized or a combination thereof in vivo is unclear. The surface-bound CXCL12 distribution has been examined in vivo by antibody staining [6] or by imaging CXCL12-GFP knock-in mice [41]; however, information about soluble CXCL12 is currently inaccessible. Studies have suggested that the chemokine CCL21 is bound to extracellular matrix or to cell membranes through interactions with glycosaminoglycans (GAGs).…”
Section: Discussionmentioning
confidence: 99%
“…The chemotactic effects of CXCL12 on T cells is well established, yet whether active CXCL12 is soluble, immobilized or a combination thereof in vivo is unclear. The surface-bound CXCL12 distribution has been examined in vivo by antibody staining [6] or by imaging CXCL12-GFP knock-in mice [41]; however, information about soluble CXCL12 is currently inaccessible. Studies have suggested that the chemokine CCL21 is bound to extracellular matrix or to cell membranes through interactions with glycosaminoglycans (GAGs).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is expressed constitutively in a large array of tissues such as heart, lung, liver, and spleen [9][10][11][12]. Its ligand is stromal cellderived factor-1a (SDF-1a) [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…CCR7, which determines the accumulation of Ag-loaded mature DCs in T cell-rich areas, is upregulated (25,(33)(34)(35)(36). A recent study also suggested that CXCR4-and CCR7-mediated signaling might cooperatively regulate the migration of DCs into the splenic white pulp (37). Inhibiting the migration of DCs has been used to treat immune diseases.…”
Section: Discussionmentioning
confidence: 99%